(untitled) (Research, Society and Development, 2019)
Data science is constantly evolving, but many problems are sometimes impossible to solve, either because of the large amount of data collected or associated with different types of data, by stating that there are several problems that can not be solved by processing issues , and to observe that the flood of data only increases every day, the following question remains: What path can data science follow in order to manage the issue of the processing limit given in increasingly exorbitant quantities? This article aims to suggest a possible future solution to the problem through descriptive research, through documentary analysis. Following the following steps: Basic theoretical background on Data Science, NoSQL Database, Big Data, Machine Learning and the Quantum Computer, aiming at pointing out future steps or possible problems.